Inappropriate use of proton pump inhibitors increases cardiovascular events in patients with coronary artery disease - Forero, Juan Riofrío; Freile, Edison Haro; Arteaga, Esteban Maggi; Cordova, Juan García; Romero, Gloria Loor; Molina, Paula Vásconez; Cadena, Marilyn Leon (International Journal of Research in Medical Sciences, 2025)
Various antiplatelet drugs are currently a cornerstone of treatment for various coronary artery diseases. They help control disease progression, but they can also increase the risk of gastrointestinal bleeding. Various clinical practice guidelines recommend the use of proton pump inhibitors (PPIs) to reduce the risk of gastrointestinal bleeding in patients receiving dual antiplatelet therapy. However, in people at low risk of gastrointestinal bleeding, the harms associated with routine PPI use may far outweigh the benefits. PPIs increase the risk of gastrointestinal bleeding, inhibit the effect of antiplatelet agents, impair vascular endothelial function and induce hypomagnesemia, iron deficiency and vitamin D and K deficiencies. Furthermore, PPIs can increase cardiovascular events. This review elucidates the mechanisms by which PPIs increase cardiovascular events, reminding physicians of the importance of prescribing them rationally.